The Seven Sustainability Competences according to the RESFIA+D Model. Part B: Practical Experiences - Niko Roorda; Anouchka Rachelson (The Central European Review of Economics and Management (CEREM), 2019)
Aim: In a previous article within this same journal, called 'The Seven Sustainability Competences according to the RESFIA+D Model. Part A: Conceptual background ', the origins, structure and validation were described of a model for professional competences for sustainable development, called RESFIA+D.The model provides an assessment and policy instrument that can easily be applied practically. Examples of such applications are offered in the current article.Companies, NGO's and other organizations may apply RESFIA+D as a structured tool for human resource development (HRD). Institutions for higher and vocational education can use the instrument for education (re)development, where curricula and didactic approaches are derived from a systematically designed competence profile in which sustainable development is integrated. Finally, individual professionals may use RESFIA+D as a tool for professional development.~Design / Research methods:The practical applications described in this article offered a way to evaluate and improve the RESFIA+D model, which contributed to the validation process of the assessment tool.~Conclusions / findings:Based on reactions of users, it is concluded that the RESFIA+D assessment is helpful to enable organizations and individual professionals to understand their strengths and weaknesses in their competences in relation to sustainable development; and to enable educational institutions, e.g. universities, to improve their educational goals, competence profiles and curricula related to sustainable development.~Originality, value of the article:The article focuses in a unique way on the roles of individual professionals towards sustainability, whereas most or all usual assessment models focus on the roles of either entire organizations, or of individual persons seen as civilians or customers.
Keywords: I20; I23; J24; Q01; Q56; 330; Competences; Sustainable Development; RESFIA D; Human Resource Development (HRD); Professionals; Organizations; Education